Dataset for "Phenotypic integration and modularity drives skull shape divergence in the Arctic fox (Vulpes lagopus) from the Commander Islands" - Martín-Serra, Alberto; Nanova, Olga; Varón-Gonzalez, Ceferino; Ortega, Germán; Figueirido-Castillo, Francisco Borja (The Royal Society, 2019)
La base de datos hace referencia al artículo: Martín-Serra A, Nanova O, Varón-González C, Ortega G, Figueirido B. 2019 Phenotypic integration and modularity drives skull shape divergence in the Arctic fox (Vulpes lagopus) from the Commander Islands. Biol. Lett. 15: 20190406. En ella se proporciona las coordenadas de los landmarks digitalizados en los cráneos de la especie Vulpes lagopus.
Keywords: Zorros; Interacción genotipo-medio ambiente; Fenotipo; Landmarks coordinates; Skull shape; Vulpes lagopus